Educational inclusion and satisfaction of families of students with intellectual disabilities: a bibliometric study - Tebar-Yébana, Susana; Navarro-Mateu, Diego; Gómez-Domínguez, María Teresa; Gómez-Dominguez, Valentina (Frontiers in Psychology, 2024)
This bibliometric study scrutinizes the corpus of scientific output within the Web of Science pertaining to familial satisfaction among parents raising children with intellectual disabilities, focusing specifically on the milieu of educational inclusion. The analysis discerns a discernible ascension in scholarly interest in this domain, encapsulating 77 papers emanating from 75 journals, incorporating an aggregate of 3,497 cited references. Our investigation delineated 354 researchers across 39 nations, underscoring the transnational purview of this scholarly endeavor. The United States emerged as the pre-eminent contributor, with Canada and the United Kingdom following suit. Collaboration on an international scale was notably led by the US, with the UK and Australia trailing in tandem. Prominent institutions were identified for their scholarly output; the University of Kansas led with four papers, followed closely by Monash University, University of California Los Angeles, and University of California Riverside, each contributing three papers. Of particular note, the University of Kansas accrued 250 global citations (TGCS). A total of 75 journals were encompassed in this study. The Journal of Intellectual Disability Research emerged as the vanguard with four published papers, closely trailed by Child Care Health and Development and Exceptional Children. Notably, the latter boasted the highest impact factor (JCR = 4.09; Q1). In summation, this review proffers a meticulous and expansive overview of extant scholarship concerning the experiences of families rearing children with disabilities within the inclusive education framework.